2023
DOI: 10.1002/adom.202203070
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Effect in Brunel Harmonic Generation in Thin Film Organic Semiconductors

Abstract: Nonlinear optical properties of organic semiconductors (OSCs) have been extensively investigated in the perturbative regime, while strong light induced high‐order processes in solid‐state OSCs are less studied. Here, below‐threshold harmonic generation is examined, both experimentally and theoretically, in two solid‐state thin film OSCs, that is, tetraphenylporphyrin and zinc tetraphenylporphyrin. Results show that the π–π* excitations of the porphyrin ring system generate the harmonic emission. The contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“… 89 Recently, the code has been extended to simulate high harmonic generation (HHG) spectra under intense laser pulses and was utilized to complement and analyze the pulse-induced electron dynamics in the organic semiconductor molecules tetraphenylporphyrin (TPP) and zinc-tetraphenylporphyrin (ZnTPP). 326 Figure 19 shows the good agreement of the experimental absorption and HHG spectra with the calculated ones. The difference in the first few harmonics is due to the fact that the experimental spectra contain contributions from the quartz substrate.…”
Section: Recent Developmentsmentioning
confidence: 55%
See 3 more Smart Citations
“… 89 Recently, the code has been extended to simulate high harmonic generation (HHG) spectra under intense laser pulses and was utilized to complement and analyze the pulse-induced electron dynamics in the organic semiconductor molecules tetraphenylporphyrin (TPP) and zinc-tetraphenylporphyrin (ZnTPP). 326 Figure 19 shows the good agreement of the experimental absorption and HHG spectra with the calculated ones. The difference in the first few harmonics is due to the fact that the experimental spectra contain contributions from the quartz substrate.…”
Section: Recent Developmentsmentioning
confidence: 55%
“…Our simulations combined with experiments showed that π → π* excitation plays a major role in the harmonic generation process in porphyrins. It was also discovered that resonant excitation leads to an early onset of nonperturbative behavior for the fifth harmonic, and similar effects are expected in Brunel harmonic generation with other organic materials …”
Section: Recent Developmentsmentioning
confidence: 66%
See 2 more Smart Citations
“…Third, high harmonics have also been explained by intraband currents where the nonlinearity enters through the nonparabolic shape of the conduction (and valence) bands . Fourth, the nonlinearity that is inherent to the process of photoionization was proposed as a possible origin for harmonic generation. , Three possible ionization-related mechanisms have been discussed in the context of HHG. , Brunel harmonics, arising from the acceleration of quasi-free carriers excited by photoionization, have been analyzed in gases, clusters, bulk solids, and thin films. Moreover, after nonresonant photoionization an excited electron has nonzero velocity, which provides subcycle contributions to the polarization and gives rise to the generation of harmonics. However, the strength of these velocity harmonics is expected to be insignificant under typical experimental conditions due to the modest photon energies that result in small excess velocities.…”
Section: Introductionmentioning
confidence: 99%